Evaluation of Geometric Parameter Variations in GMAW Weld Joints on SPA-H Steel: A Statistical and Practical Perspective - Mochammad Igo Syamsari Sutaji; Subagiyo (Universitas Muhammadiyah Metro, 2026)
Gas Metal Arc Welding (GMAW) is widely used in the manufacturing industry for its efficiency in producing high-quality weld joints. However, the mechanical properties of these joints are strongly influenced by geometric parameters such as root gap and bevel angle. This study investigates the combined effect of root gap and bevel angle variations on the tensile and bending performance of GMAW joints using low-carbon corrosion-resistant SPA-H steel (JIS G3125). A full factorial design was employed with three levels of root gap (4 mm, 6 mm, 8 mm) and bevel angle (40°, 47.5°, 55°). Tensile, bending, and macrostructure tests were conducted, and data were analyzed using Minitab 19. Although statistical analysis (ANOVA) indicates no significant effects, practical trends reveal that the 8 mm root gap and 55° bevel angle configuration achieved the highest tensile strength (571.82 MPa) and exhibited no visual defects during the bending test. This configuration is identified as the optimal parameter setting for GMAW of SPA-H steel due to its superior mechanical integrity and weld quality.Keywords: bevel angle, GMAW welding, root gap, SPA-H steel, tensile strength,